Role of Fatigue and Creep in Structural Damage: A Comprehensive Review - Purva Taksalkar (International Journal of Fracture Mechanics and Damage Science, 2025)
Fatigue and creep are two critical degradation mechanisms that significantly influence the structural integrity and longevity of engineering materials. These phenomena arise due to different loading and environmental conditions but often coexist in various industrial applications, leading to severe material degradation over time. Fatigue primarily results from cyclic loading, where repeated stress variations induce microstructural damage and crack initiation, ultimately causing catastrophic failure. Conversely, creep occurs under sustained stress at elevated temperatures, leading to progressive deformation and time-dependent strain accumulation. Understanding these mechanisms is vital for predicting service life and preventing unexpected structural failures. This review comprehensively examines the fundamental principles underlying fatigue and creep, delving into their individual and combined effects on material performance. It explores how different materials respond to these degradation mechanisms, the factors influencing their susceptibility, and the microscopic processes governing failure. Additionally, the article evaluates experimental methodologies employed to study fatigue and creep, ranging from traditional mechanical testing to advanced non-destructive evaluation techniques. Predictive models play a crucial role in assessing fatigue and creep behavior, with numerous mathematical frameworks developed to estimate life expectancy and failure probabilities. This review discusses classical and contemporary models used in engineering practice, emphasizing their applicability to different materials and loading conditions. Furthermore, recent advancements in material science and engineering strategies aimed at mitigating fatigue and creep damage are explored. Innovations in alloy design, surface treatments, and structural health monitoring contribute significantly to enhancing material resilience. Case studies from diverse industries, including aerospace, civil engineering, and power generation, illustrate the practical consequences of fatigue and creep damage. The review concludes with a discussion on future research directions and recommendations to improve material durability, ensuring safer and more reliable engineering applications.
Keywords: Material degradation; Structural health monitoring; advanced materials; cyclic loading; life cycle prediction; structural integrity